Continuous-culture fermentation as a tool for forage evaluation - E.S. Vanzant; R.C. Cochran; S. Stafford; G. St Jean; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 1994)
Ruminal degradation of organic matter and protein in alfalfa and prairie hay were evaluated in vivo, using cannulated cows, and in vitro, using a continuous-culture fermenter to simulate ruminal fermentation. Estimates of organic matter degradability, microbial N flow per unit feed N input, and efficiency of microbial growth were not different (P>.10) between the in vivo and in vitro systems. However, for both forages, estimates of nitrogen degradability were greater with the in vitro system. Despite the differences between in vivo and in vitro techniques for some variables, continuous-culture fermentation will allow us to compare the effects of dietary treatments on forage digestion and will aid in the formulation of supplements to meet specific nutrient requirements for cattle consuming forage-based diets.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Alfalfa; Prairie hay; Ruminal digestion; Protein